Literary Representation of Women in Khaled Hosseini’s A Thousand Splendid Suns - Verma, Sumit Raj (Patan Prospective Journal, 2023)
The study examines the difficulties that women in Afghanistan encounter in society and culture as depicted in Khaled Hosseini's A Thousand Splendid Suns. The novel revolves around Mariam and Laila, two Afghan women who are the main female characters in the story. Even though their lives were different at first, the war in Afghanistan and the Taliban-led government have made their lives worse. The main focus of this paper is to analyze the female characters and their resistance against the oppression of women in patriarchal societies. The thesis aims to explore the oppression experienced by women and the challenges that main female characters face in confronting the oppression from male characters as depicted in the novel. This research employs Islamic feminism as a theoretical framework to analyze the text, focusing on women's studies. The novel depicts how the rigid and intolerant religious beliefs in Afghanistan are hindering the exposure and advancement of women in society.